Radiological changes in the thymus in patients who have had covid-19 and in vaccinated persons who have not had covid-19: a ct study - Tuğtağ Demir, Berin; Metin Söğütlügil, Melike Ruşen (My University, 2024)
Background: There are very few and limited studies on the role of the thymus in COVID-19 infection. It is known that thymus morphology changes in individuals vaccinated against COVID-19 although they do not have active infection. Objective: Our study aims to evaluate these differences in detail. Methods: This research was conducted in a total of 141 people, 75 women and 66 men. The research consisted of three groups: unvaccinated persons who have had the disease (n = 49), vaccinated persons who have not had the disease (n = 37), and unvaccinated persons who have not had the disease (control group, n = 55). In the study, the thymus volume, structure, and fat content were investigated and the differences between groups were evaluated. Results: Thymus volume was greatest (0.43 ± 0.11) in the vaccinated group that had not had the disease and smallest (0.15 ± 0.07) in the unvaccinated group that had had the disease, and a significant difference was found between the groups. Thymus steatosis was seen mostly in the unvaccinated group that had had the disease (72%; p = 0.04). The diffuse nodular pattern was only present in the diseased group. Conclusion: This research is the first study in the literature to date on the effect of COVID-19 and vaccines on the thymus. In addition to the acute consequences of the virus, the possibility of negative symptoms after COVID-19 should also be kept in mind, especially in unvaccinated people. Further studies are needed to confirm the results reported herein.
Morphologische veränderungen im thymus bei covid-19-patienten und geimpften: ct-studie
Keywords: Computerized Tomography; COVID-19; Morphology; Thymus; Vaccination